Securing the Sarawak Kalimantan Frontier: Navigating Dilemma and Strategic Approaches - Nurul Huda, Marwan; Mohd Kamarulnizam, Abdullah; Shazwanis, Shukri (Zhongguo Hangtian Gongye Zonggongsi, 2023)
Securing vast and porous border regions, exemplified by the 1,645 kilometres stretch between Sarawak (Malaysia) and Kalimantan (Indonesia), poses unique and formidable dilemmas for security agencies. This shared boundary encompasses diverse geographical features, including rivers, vast land expanses, rugged terrains, and dense forests, which pose significant challenges for authorities to efficiently control and monitor the movement of people and goods. Furthermore, because of its remote geographical location, this border area is vulnerable to non-traditional security threats, such as encroachment, human and goods smuggling, and trafficking. This study delves into the complexities of border security in Sarawak by employing in-depth interviews with various security agencies and on-site observations to comprehensively examine and address these dilemmas. The findings of the study highlight how difficult topographical conditions at these borders have hampered efficient border control measures, such as building fences and barriers, deploying CCTV surveillance, and establishing border control stations. This has made it difficult for authorities to monitor and track the entry and exit of individuals and goods, contributing to the emergence of illegal pathways known as 'jalan tikus' and 'jalan gajah' by locals, giving rise to cross-border crime activities. In addition, this study outlines other issues faced by border security agencies, such as a lack of resources, manpower, advanced technology, border conflicts, and constraints on military authority. By shedding light on these multifaceted dilemmas, this research contributes to a broader understanding of the border security complexities in the Sarawak-Kalimantan region. These findings underscore the critical need for a comprehensive approach to effectively safeguard borders and mitigate associated risks, thus providing a valuable resource for guiding future endeavours in border security management.